Menopausal metabolic syndrome and the risks of menopausal hormone therapy: the solutions - A.E. Esedova; N.G. Urudzheva; I.Yu. Ilina (РМЖ. Мать и дитя, 2020)
A.E. Esedova1, N.G. Urudzheva1, I.Yu. Il’ina2 1Dagestan State Medical University, Makhachkala, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Climacteric is a physiological period of woman’s life starting from the decline in ovarian activity until the end of ovarian function. This period is commonly accompanied by the development of menopausal metabolic syndrome characterized by the increase in visceral fat mass, insulin resistance, and hyperinsulinemia which result in the disorders of carbohydrate, lipid, and purine metabolism. This paper reviews the factors increasing the risk of metabolic syndrome during menopause. Diagnostic techniques for metabolic syndrome are described. Treatment approaches to menopausal metabolic syndrome, the potentialities and specifics of menopausal hormone therapy (MHT), its anticipated effects are discussed. The difficulties with MHT are accounted for by the lack of an optimal medication which will maintain the functioning of cardiovascular system, skeletal system, brain, and optimal weight and also has a minimal risk of side effects and complications. Meanwhile,  adequate MHT for climacteric disorders in perimenopausal and early postmenopausal women is an effective and safe treatment for menopausal metabolic syndrome considered as a prerequisite for cardiovascular diseases and type 2 diabetes. Keywords: menopause, climax, metabolic syndrome, obesity, hypertension, diabetes, menopausal hormone therapy, venous thromboembolism. For citation: Esedova A.E., Urudzheva N.G., Il’ina I.Yu. Menopausal metabolic syndrome and the risks of menopausal hormone therapy: the solutions. Russian Journal of Woman and Child Health. 2020;3(4):260–266. DOI: 10.32364/2618-8430-2020-3-4-260-266.